1989
DOI: 10.1017/s0016672300028500
|View full text |Cite
|
Sign up to set email alerts
|

P-element transposase induces male recombination inDrosophila melanogaster

Abstract: SummaryMale recombination in P–M dysgenic crosses has been viewed as a reflection of P-element transposase interacting with P elements. However, recent studies suggest that the transposase may catalyse double-stranded breaks in chromosomal DNA. We have, therefore, introduced P(Δ2–3 ry+) (99B), a single non-mobile P-element transposase source, into the long-standing laboratory true M strains of a flanking lethal crossover selective system, thus facilitating the examination of rare male recombination events as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Similar to local transposition, P-induced male recombination occurred mostly near the starting element (Duttaroy et al 1990;McCarron et al 1994;. The HEI sites were also frequent Pinsertion targets (Figure 3).…”
Section: Resultsmentioning
confidence: 93%
“…Similar to local transposition, P-induced male recombination occurred mostly near the starting element (Duttaroy et al 1990;McCarron et al 1994;. The HEI sites were also frequent Pinsertion targets (Figure 3).…”
Section: Resultsmentioning
confidence: 93%
“…In this study, excision events are shown to be independent of the crossover events, as are P(lArB) retention events. However, since transposase has been shown to induce crossovers in the absence of a Pelement (McCarron et al, 1989(McCarron et al, , 1994, we need to invoke a prior excision to explain the P-retaining crossovers. The excision process itself is not precise; indeed, precision is rare (Tsubota and Schedl 1986;O'Brochta et al, 1991;Takasu-Ishikawa et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of exchange of transposase-initiated crossovers in D. melanogaster males increased when two transposase producers were used. Finally, the crossover distribution of transposase-induced events corresponded with the cytological map of the metaphase chromosome (McCarron et al, 1994). The introduction of a P-element target, with its highly specific transposase binding site, has been shown to produce a marked crossover increase in the P element target region Preston and Engels, 1996;Tanaka et al, 1997) as well as a significant increase in regions genetically distinct from the target (Duttaroy et al, 1990;McCarron et al, 1994).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations